Sense of Coherence or resilience as predictors of psychological distress in nursing students during the COVID-19 pandemic - Hasimi, Leila; Ahmadi, Mehrnaz; Hovyzian, Shahla Assadi; Ahmadi, Ali (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic lead to the occurrence of numerous psychological distress among students. This study aimed to determine the level of psychological distress as well as the predictive role of Sense of Coherence (SOC) and resilience in nursing students. Methods A cross-sectional descriptive study was conducted on 310 nursing students in Ahvaz Jundishapur University of Medical Sciences, Iran. The data of the study was collected through the demographic information questionnaire, the General Health Questionnaire (GHQ), the Academic Resilience Inventory (ARI), and the Sense of Coherence Scale (SOC-13). Results Students' mean scores for the GHQ, ARI, and SOC were 5.81 ± 1.37, 102.88 ± 11.91, and 54.54 ± 6.46, respectively. Regression models showed that two domains of SOC [meaningfulness (β = −0.28, p < 0.001), manageability (β = −0.19, p = 0.001)], female gender (β = 0.12, p = 0.015), and overall ARI (β = −0.12, p = 0.037), were significantly associated with the GH of nursing students. SOC domains [meaningfulness (β = −0.19, p = 0.002), manageability (β = −0.15, p = 0.006)], problem-oriented/positive thinking domain of ARI (β = −0.15, p = 0.011), sex (β = 0.12, p = 0.015), and history of death in first-degree relatives (β = 0.12, p = 0.021) were significantly associated with social dysfunction domain of GH. Three domains of SOC [meaningfulness (β = −0.26, p < 0.001), manageability (β = −0.13, p = 0.032), and comprehensibility (β = −0.13, p = 0.039)], were significantly associated with psychological distress domain of GH. Conclusion Our results indicated that low SOC and resilience were predictors of psychological distress in nursing students. Accordingly, interventions such as teaching stress management skills, the skills of using positive coping methods in dealing with stressful situations, and self-management skills are necessary to improve the level of resilience and SOC in nursing students.